Fuzzy adaptive resonance theory failure mode effect analysis non-healthcare setting for infectious disease: review - Aysha, Samjun; Kasumawati, Lias; Mohd. Zulhilmi, Firdaus Rosli; Hazrul, Mohamad Basri; Chai, Chee Shee; Kuryati, Kipli (Institute of Advanced Engineering and Science (IAES), 2023)
Fuzzy adaptive resonance theory (ART) is an ART network that is developed as one of the alternative methods to evaluate risk priority number (RPN) in failure mode and effect analysis (FMEA). Not only is FMEA are common technique as an analysis tool in industrial sectors, but also, especially during the global emergency COVID-19 pandemic hits, FMEA is used in prevention and mitigation measures. Many alternative methods have been proposed. However, not many investigations use clustering models such as Fuzzy ART in FMEA. This paper aims to provide a comprehensive review and then propose a model for systematic risk analysis which implement the fuzzy ART model, named clustering- transmission causes and effects analysis (c-TCEA), for the prevention and mitigation of infectious diseases.